Import price dynamics in major advanced economies and heterogeneity in exchange rate pass-through - Stéphane Dées; Matthias Burgert; Nicolas Parent (European Central Bank (ECB), 2008)
This paper aims at showing heterogeneity in the degree of exchange rate pass-through to import prices in major advanced economies at three different levels: 1) across destination markets; 2) across types of exporters (distinguishing developed economy from emerging economy exporters); and 3) over time. Based on monthly data over the period 1991-2007, the results show first that large destination markets exhibit the lowest degree of pass-through. The degree of pass-through for goods imported from emerging economies is also significantly lower than for those from developed economies. Regarding the evolution over time, no clear change in pricing behaviours can be identified and particular events, like large exchange rates depreciations during the Asian crisis, seem to influence the degree of pass-through related to imports from emerging economies.
Keywords: E31; F3; F41; 330; Exchange Rate Pass-Through; Import price modeling; Pricing to Market; Inflationskonvergenz; Exchange Rate Pass-Through; Import; Marktgröße; Industrieländer; Entwicklungsländer